History Education in the Formation of Social Identity : Toward a Culture of Peace - Korostelina, Karina V.; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2013)
In order to determine how history education can be harnessed to reduce conflict attitudes and intentions and create a culture of peace, this book examines how history curricula and textbooks shape the identities of their students through their portrayals of ingroup and outgroup identity, intergroup boundaries, and value systems.
Keywords: Science; Science, general